2020
DOI: 10.1007/s00268-020-05510-5
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Sepsis Places a Massive Burden on Regional and Tertiary Surgical Services in KZN Province South Africa

Abstract: Background Frequently, surgical intervention is needed to treat soft tissue sepsis (STS). Ideally, most STS should be managed at the lowest level of surgical care close to the patient's home and a well‐functioning surgical service will be able to deliver this safely and effectively. This study interrogates the burden of STS in the province of KwaZulu‐Natal and reviews at which level in the health system the operative management of STS is being dealt with. Methods This study describes the operations for soft ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This suggests that district hospitals are not providing the expected level of surgical care and that this workload is being transferred to higher levels of care. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that district hospitals are not providing the expected level of surgical care and that this workload is being transferred to higher levels of care. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Surgery provides immediate and transformative treatment for many health conditions and will remain a key therapeutic strategy in all countries 1 2. While surgery is performed in every community, wealthy and poor, rural and urban and in all regions with an estimated 234 million major surgical procedures performed annually,3 4 it is also a major source of avoidable morbidity and mortality worldwide 5 6. Recent studies have revealed a global surge in surgical procedures and indicated that expanding access to surgeries in low and middle-income countries (LMICs) has the potential to avert 1.4 million fatalities and reduce the burden of 77.2 million disability-adjusted life years each year 7.…”
Section: Introductionmentioning
confidence: 99%